BUILDING A COMMUNITY LEGACY TOGETHER: EVALUATION OF INTERGENERATIONAL WISDOM PROJECT. (11th November 2018) - Pillemer, K; Schultz, L; Cope, M; Wassel, M; Yau, H
Abstract: As their numbers are increasing, older people struggle with a lack of opportunities for social integration and participation in meaningful activities and relationships. Similarly, research shows that teenagers have limited contact with older people. Thus, the opportunity for older individuals to share practical advice and wisdom with the younger generation has declined precipitously over the past half century. To address this issue, the Building a Community Legacy Together (BCLT) project breaks new ground by testing an innovative model for intergenerational programming, based on current research on elder wisdom and on youth development. In the BCLT, high school age youth are trained to: 1) conduct face-to-face interviews with older adults, age 65+, regarding their advice or lessons for living; 2) summarize the interview data; and 3) create and present a report to the community. We report on the evaluation of the project, in which total of 239 youth and 201 older persons were assigned to treatment or control conditions There were significant differences between pre-test and post-test scores for the youth treatment group. Specifically, youth participants improved on attitudes toward older people and in their sense of life purpose whereas control group members did not. No significant effects were found for the older participants. Implications for future evaluation of intergenerational programs is discussed, including the feasibility of randomized, controlled designs in evaluating intergenerational programs.